Review : Formulasi dan Evaluasi Tablet Hisap dan Tablet Effervescent dari Ekstrak Bahan Alam dengan Berbagai Metode Formulasi - Adila Abadi, Shada; Reihan Ridha, Muhammad; Savitri, Aida; Nisa, Jannatun; Saputra, Nicky; Latifah, Nor (LP4M STIKes Karsa Husada Garut, 2024)
Introduction: Indonesians have long recognized and used medicinal plants to treat health problems. The use of natural products, especially from plants, increased by 380%. The use of natural ingredients from plants is generally still done traditionally, such as brewing, mashing, or taking the juice, which makes it difficult to determine a uniform dose, so there is a high possibility of non-uniformity in the composition of the compounds in the final product. Therefore, this is an impetus for traditional medicine manufacturers to create practical preparations, one of which is by making tablet preparations such as lozenges and effervescent tablets from natural ingredient extracts. Method: This article review is based on references from several nationally published database articles and online search instruments. Result: Based on the results of the review of several articles, 8 journals were selected that met the predetermined criteria. Conclusion. From the results of the review, it is known that natural ingredient extracts can be formulated into several types of tablet preparations such as lozenges and effervescent tablets using wet granulation, dry granulation, and direct felting methods and evaluation of tablet preparation is carried out to ensure the quality of tablet preparations. Keywords: Formulation, tablet, extract, evaluation